The Importance of Attracting Investments in the Development of a Green Economy (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article provides a comprehensive analysis of Uzbekistan’s transition to a green economy, the challenges encountered along the way, and the importance of attracting investments. The green economy is presented as a modern economic model that integrates environmental sustainability, economic growth, and social welfare. The article emphasizes the crucial role of investments in the transition to a green economy, particularly in renewable energy sources, environmental technologies, innovation, and healthcare sectors. Based on literature review, statistical data, and decision-making processes, the study examines the economic, environmental, and social impacts of attracting investments in the green economy within the context of Uzbekistan. The transition to a green economy is substantiated as a key factor for Uzbekistan’s long-term development, environmental security, and social well-being.